Renewal of the Epistemology of Fiqh by Hasbi Ash-Shiddieqy and Its Implementation in Minority Muslim Communities - Jamal, Jamal; Al Ahmadi, Fahad Muhanna Salem (Peradaban Journal of Law and Society, 2023)
This study aims to elucidate the contributions of TM. Hasbi Ash-Shiddieqy to the renewal and development of Ushul fiqh in the Indonesian archipelago, along with its actualization in minority Muslim regions. TM. Hasbi Ash Shiddieqy is recognized as one of the influential figures in the early development of Islamic law in post-independence Indonesia. This qualitative research employs a library research approach. The findings reveal that in his ijtihad, TM. Hasbi Ash-Shiddieqy underscores the importance of Urf, Maslahah Mursalah, and Sad Adzariah, aiming to make Islamic laws more flexible, adaptive, and practically applicable. The realization of Hasbi Ash Shiddieqy's thoughts in minority Muslim communities results in an adaptive, inclusive Islamic legal framework that provides concrete solutions to the challenges of diversity within minority Muslim communities.